An inventory of healthy weight practices in federally funded haemophilia treatment centres in the United States. (16th March 2014) - Adams, E.; Deutsche, J.; Okoroh, E.; Owens‐McAlister, S.; Majumdar, S.; Ullman, M.; Damiano, M. L.; Recht, M.; the Healthy Weight Working Group
Summary In the haemophilia population, obesity has an adverse effect on health care cost, chronic complications and joint disease. Although staff of federally funded Hemophilia Treatment Centers in the United States (HTCs) anecdotally recognize these outcomes, practices to promote healthy weights have not been reported. This evaluation identifies routine practices among HTCs in body mass index (BMI) assessment, perceptions about need to address obesity and roles in offering evidence‐based strategies to promote healthy weights. A telephone survey was developed to assess HTCs practices including patient BMI assessment and counselling, perceptions about the importance of healthy patient weights, and HTCs roles in weight management. Ninety of the 130 federally funded HTCs contacted elected to participate and completed the telephone survey. Of these, 67% routinely calculated BMI and 48% provided results to patients. Approximately one‐third classified obesity correctly for children (30%) and adults (32%), using the Centers for Disease Control and Preventions BMI cut‐offs. Most HTCs (87%) reported obesity as an issue of 'big' or 'moderate' concern and 98% indicated HTC responsibility to address this issue. Most centres (64%) address patient weight during comprehensive visits. One‐third (33%) of centres include a nutritionist; of those without, 61% offer nutrition referrals when needed. Most (89%) HTCs do not have a protocol in place to address healthy weights; 53% indicated that guidelines are needed. HTCs offer services to help improve weight outcomes. Training programmes for calculating and interpreting BMI as well as identifying appropriate guidelines to apply to the HTC patient population are needed.